Combined experimental and first-principles studies of a hydrated uranyl carbonate: Insight into phonon spectra for a core environmental class of uranium materials. (March 2020) - Kalashnyk, N.; Perry, D.L.; Ivanov, V.G.; Faulques, E.
Abstract: Density functional theory calculations for an environmentally important crystalline phase of a hydrated uranyl carbonate, liebigite (Ca2 UO2 (CO3 )3 ·11H2 O), were performed at the generalized gradient approximation Perdew-Burke-Ernzherhof functional level to support experimental interpretation of vibrational data. This phase contains the uranyl tricarbonate center (UO2 (CO3 )3 4− ), which represents the coordination core of many uranium materials found in nature. This hydrated crystal is surprisingly found to have a theoretical band gap of about 2.45 eV. The electronic structure shows strong covalent U–O and C–O bonds accounting for the marked relative intensity of the Raman bands. Vibrational and photoluminescence spectra are presented. Original assignments of the vibrational lines are proposed on the basis of the theoretical analysis of the normal modes. The role of water in the vibrational properties of the crystal is discussed by investigation of, in particular, a "dry" hypothetical framework structure without water molecules. Graphical abstract: Image 1 Highlights: Hydrated calcium-containing uranyl tricarbonate crystal investigated with periodic density functional theory (DFT). Structural, electronic, vibrational, and dynamical properties determined for a 200-atom primitive cell. Description of infrared, Raman, and photoluminescence spectra in relation to solid-state DFT results from 0 to 3600 cm −1 . Vibrational assignments revisited, and phonon density of states discussed. Comprehensive understanding of the role of the water molecules in the structure of liebigite.